Efficient method for the synthesis of acylals from aldehydes under solvent-free conditions catalyzed by antimony trichloride - Bhattacharya, Asish K.; Mujahid, Mohammad; Natu, Arvind A. (Synthetic Communications, 2008)
A mild and efficient method has been developed for the preparation of acylals from aldehydes catalyzed by antimony trichloride under solvent-free conditions in very good to excellent yields. The easy availability, low cost, and ease of handling of the catalyst make this procedure especially attractive for large-scale synthesis.
Keywords: acetic anhydride; Acylals; aldehydes; antimony trichloride; solvent-free conditions